Tsvetaeva's tragedy Ariadne: Stage performance experience - D. D. Kumukova (Шаги, 2022)
The article examines Tsvetaeva's tragedy Ariadne and the difficulties of its stage performance. Analysis of the musical organization of the verse shows that the melodic-rhythmic structuring of direct speech creates the illusion of theatrical performance. That is, even at the level of the verbal text the intonation and, in a broad sense, the plastic pattern of the action can be discerned. The effect of stage implementation is also facilitated by the use of various genres of Russian folklore with their ritual nature. Moreover, through musical techniques images are created and a dramatic conflict is formed. Thus, the system of Tsvetaeva's keynote ideas makes it possible, through the poetic refrain, to “sound” the voice of fatality, presaging the tragic denouement. The 2001 performance of Ariadne on the stage of the St. Petersburg Theater of Satire on Vasilievsky Island took into account this musical nature of the play. The director Svetlana Svirko found her musical key, which for the first time in the history of Tsvetaeva's tragedy opened the way to its theatrical performance. Svirko staged the performance as an opera, where the choir became the main character. In the vocal and dance part of the choir, in fact, a ritual act was reproduced, revealing an ancient tragic shape. Thus, in a play of the twentieth century, the performance uncovered the nature of ancient art, revealed the genealogy leading to the choral origins of ancient theater and gave a definite answer to a question that in one form or another has been considered by researchers — namely, about the scenic character of Tsvetaeva's Ariadne.